Niche partitioning of microbial communities in riverine floodplains - Peipoch, Marc (Sci Rep, 2019)
Riverine floodplains exhibit high floral and faunal diversity as a consequence of their biophysical complexity. Extension of such niche partitioning processes to microbial communities is far less resolved or supported. Here, we evaluated the responses of aquatic biofilms diversity to environmental gradients across ten riverine floodplains with differing degrees of flow alteration and habitat diversity to assess whether complex floodplains support biofilm communities with greater biodiversity and species interactions. No significant evidence was found to support a central role for habitat diversity in promoting microbial diversity across 116 samples derived from 62 aquatic habitats, as neither α (H’: 2.8–4.1) nor β (Sørensen: 0.3–0.39) diversity were positively related to floodplain complexity across the ten floodplains. In contrast, our results documented the sensitivity of biofilm communities to regional templates manifested as gradients of carbon, nitrogen, and phosphorous availability. Large-scale conditions reflecting nitrogen limitation increased the relative abundance of N-fixing cyanobacteria (up to 0.34 as fraction of total reads), constrained the total number of interactions among bacterial taxa, and reinforced negative over positive interactions, generating unique microbial communities and networks that reflect large-scale species sorting in response to regional geochemical gradients.